KUALITAS ASAP CAIR BATANG GELAM (Melaleuca sp.) - Alpian; Tiberius Agus Prayitno; Johanes Pramana Gentur Sutapa; Budiadi (Jurnal Penelitian Hasil Hutan, 2014)
Gelam (Melaleuca sp.) is a tidal swamp species that grows abundantly in South and Central Kalimantan swamp forest. Gelam is one potential species for wooden vinegar production as the technology is available and readily implemented. This paper studies the possible utilization of gelam wood species for wood vinegar. The vinegar was condensed during wood pyrolysis processes at the temperature of 500°C for 3 hours. Wood vinegar was yellow reddish in colour, transparant and no floating material. The vinegar specific gravity was 1.008 to 1.058 with the pH of 3.105 to 3.195 and acidity level varies from 5.167 to 12.903%. The carbonyl and phenol content were 11.250 to 30.390% and 2.429 to 9.231% respectively. In general, gelam wood can produce wood vinegar and its quality meet the Japanese standard requirements.